2022
DOI: 10.2903/j.efsa.2022.7209
|View full text |Cite
|
Sign up to set email alerts
|

The European Union Summary Report on Antimicrobial Resistance in zoonotic and indicator bacteria from humans, animals and food in 2019–2020

Abstract: Data on antimicrobial resistance (AMR) in zoonotic and indicator bacteria from humans, animals and food are collected annually by the EU Member States (MSs), jointly analysed by the EFSA and the ECDC and reported in a yearly EU Summary Report. The annual monitoring of AMR in animals and food within the EU is targeted at selected animal species corresponding to the reporting year. The 2020 monitoring specifically focussed on poultry and their derived carcases/meat, while the monitoring performed in 2019 specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
119
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(182 citation statements)
references
References 232 publications
(308 reference statements)
22
119
0
2
Order By: Relevance
“…Furthermore, S. Dublin is one of the serotypes showing the highest multidrug resistance [ 19 ]. Data from the European Food Safety Authority (EFSA) indicate ongoing and overall high levels of antimicrobial resistance regarding Salmonella in the European Union [ 47 ]. However, the results of the present study revealed no significant antimicrobial resistance of the serovar Dublin via either in vitro or in silico approaches ( Figure 1 , Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, S. Dublin is one of the serotypes showing the highest multidrug resistance [ 19 ]. Data from the European Food Safety Authority (EFSA) indicate ongoing and overall high levels of antimicrobial resistance regarding Salmonella in the European Union [ 47 ]. However, the results of the present study revealed no significant antimicrobial resistance of the serovar Dublin via either in vitro or in silico approaches ( Figure 1 , Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Campylobacter is small spiral Gram-negative bacterial pathogen and the main agent of campylobacteriosis, which is the most common zoonotic disease in the EU transmitted to humans directly from animals, or through the foodborne route [ 1 , 2 ]. Recent source attribution analysis has revealed the prevalent role of broiler chickens as the cause of human Campylobacter infections in the Baltic countries [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing resistance of thermophilic Campylobacter spp. to antibiotics could lead to detrimental effects on public health [ 2 , 17 , 18 , 19 ]; therefore, the World Health Organization has classified many of these antimicrobials as critically important for human medicine [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic is generally considered for the treatment of C. jejuni . However, with the spread of these antibiotics implemented in clinical and animal husbandry, C. jejuni isolates have obtained apparent resistance and gradually enhanced [ 5 , 6 ]. Moreover, symptoms caused by C. jejuni are also related to its virulence.…”
Section: Introductionmentioning
confidence: 99%